Design, implementation, and evaluation of Youth Peer Support Training to improve quality of life and stress among homebound and bedridden older adults - Boonyada Wongpiomoln; Chanidawadee Sayuen; Ladda Pholputta; Nitchapanrawee Phengphol (Journal of Research Development in Nursing and Midwifery, 2023)
Background: Health care provided by youth can support homebound and bedridden older adults. The purpose of this study was to develop a program for homebound and bedridden older adults in rural areas of northeastern Thailand.